some considerations on the domestic areas of the chancay culture - Van Dalen Luna, Pieter Dennis (2013)
Despite the importance acquired Chancay culture in north-central coast during the later periods (Late Intermediate Period: 1000-1470 AD and Late Horizon: 1470-1533 AD), little is known about cultural events, especially on settlement systems and spatial distribution and architecture of the same, that the few product of research conducted. In this paper, we present some considerations about Chancay domestic areas, from research conducted in domestic and residential areas in several Chancay culture sites in the Chancay Valley. Data retrieved Andoma site, in the town of Huando, allow us to define the constructive strategies of domestic function enclosures with rectangular enclosures consecutive deployed on platforms with internal storage areas rectangular, square, oval, on ground level or underground, as well as the presence of human offerings and funerary contexts that have been placed inside the enclosures.